The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ijepes.2019.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Overhead lines Dynamic Line rating based on probabilistic day-ahead forecasting and risk assessment

Abstract: Dynamic Line Rating is a technology devised to modify an overhead line's current-carrying capacity based on weather observation. The benefits of this modification may include reduced congestion costs, an increased renewable energy penetration rate, and improved network reliability. DLR is already well developed, but few papers in the literature investigate DLR day-ahead forecasting. The latter is central to DLR development since many of the decisions related to grid management are taken at least on a day-ahead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 28 publications
(38 reference statements)
0
32
0
Order By: Relevance
“…The cable temperature estimation is a widely addressed research area with applications in dynamic line rating [21], [22], [23] and lifetime estimation [24]. In addition to the thermal stress, there are models focused on the analysis of the joint influence of electrical and thermal stresses [17].…”
Section: A Related Workmentioning
confidence: 99%
“…The cable temperature estimation is a widely addressed research area with applications in dynamic line rating [21], [22], [23] and lifetime estimation [24]. In addition to the thermal stress, there are models focused on the analysis of the joint influence of electrical and thermal stresses [17].…”
Section: A Related Workmentioning
confidence: 99%
“…Under the conditions of the same ambient temperature and Al ball temperature, the forced convection heat transfer coefficients h f with different wind speeds and the natural convection heat transfer coefficient h 0 are firstly calculated according to (13), (14) and (17). Meanwhile, a variable err c is introduced to compare the difference between h 0 and h f , which is calculated by (19).…”
Section: Correlation Analysis Of Convective Heat Losses Between Al Bamentioning
confidence: 99%
“…According to the differences of monitoring data, the models of the DTR technology can be divided into two categories. The first type of DTR model, called the Weather model, calculates the conductor ampacity by directly monitoring all the weather data, including the ambient temperature, wind speed, wind direction and global solar irradiance [13,14]. A lot of sensors are needed to measure the weather data in Weather model [15].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the risk-based approach methodology in assessing of the OTL stability [21] as a probabilistic characteristic that determines normal power supply to consumers and similar researches [22]- [25] in the field of power grid reliability showed that traditional reliability targets such as SAIFI, SAIDI, EENS [26], LOLE, LOLH [27], [28] do not allow to fully evaluate and analyse the failure rate of power outages associated with climatic factors. These indices characterize the failure rate, the outage time without indicating the reason of accidents.…”
Section: Selection Of the Territory For Researchmentioning
confidence: 99%